AB0576 Features of neurological manifestations of systemic lupus erythematosus in the kyrgyz cohort of patiens. (12th June 2018) - Koilubaeva, G.; Aseeva, E.; Soloviev, S.; Reshetnyak, T.
Abstract : Background: The development of a variety of neuropsychiatric symptoms in SLE patients starts with the dysregulation of the immune system. Involvement of the CNS in the pathological process during the onset of the disease can significantly worsen the patient's condition and complicate the prognosis. Objectives: To study the features of neurological manifestations of SLE in the Kyrgyz cohort of patients. Methods: The basis of the study were the results of an initial examination of 460 patients with prospective observation, with a reliable diagnosis of SLE. Out of them, 112 patients were neurological, at the age of 30 (median) [26, 41], predominantly of Kyrgyz nationality (87), with duration of the disease from 6 months to 7 years (median – 2.0) treated in the National Cardiology and Therapy Centre named after M. Mirrakhimov (NCTC) from January 2012 to December 2017. Neurologic manifestations of SLE were diagnosed by clinical examination by a neurologist using some instrumental methods of investigation. To assess the neuropsychiatric state of patients, the classification criteria by the American College of Rheumatology (1999) were used. Neuropsychiatric disorders were diagnosed through a clinical examination by the psychotherapist using the classification of mental disorders and behavioural disorders according to ICD (International Classification of Diseases)−10. Results: The damage of the nervous system was observed in 112 (24, 305%) Kyrgyz patients from 460, mainly of the central nervous system – in 77 (68.75%), to a lesser extent – the peripheral nervous system (PNS) – in 35 (31.25%) out of 112. In half of the observed patients with CNS lesions, various neuropsychiatric disorders were registered – in 39 (50.65%) out of 77, with psychosis prevalence with visual and auditory hallucinatory syndrome – in 34 (87.18%) out of 39 patients. There were 14 patients with cerebrovascular infection (18.18%) out of 77, mainly with ischaemic stroke in the SMA basin. There was one patient with aseptic meningoencephalitis with manifestations of mild hemiparesis and with the disruption of the function of the pelvic organs in the form of mandatory urges. Symptoms of myelopathy with malfunction of the pelvic organs were registered in 9 (11.69%) patients out of 77. Five patients had symptoms of combined CNS and PNS lesions. In one of them cases the patient had encephalopolyneuroradiculopathy of the Guillain-Barre type with the phenomena of coarse tetraparesis and with disruption of the function of pelvic organs in the form of delay, with a single epicprism. Conclusions: Neurological manifestations of SLE in the majority of Kyrgyz patients were mainly caused by CNS lesions (68.75%), mostly in the form of neuropsychiatric disorders (50.65%), with a predominance of psychosis with visual and auditory hallucinatory syndrome (87.18%). Disclosure of Interest: None declared